Serum SARS-COV-2 Nucleocapsid Protein: A Sensitivity and Specificity Early Diagnostic Marker for SARS-COV-2 Infection - Li, Tao; Wang, Li; Wang, Huihui; Li, Xuemei; Zhang, Shubing; Xu, Yuanhong; Wei, Wei (Frontiers in cellular and infection microbiology, 2020)
To explore the diagnostic value of serum severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid (N) protein assay in the early stages of SARS-COV-2 infection. Serum N protein level in SARS-COV-2 infected patients and non-SARS-COV-2 infected population was measured by enzyme-linked immunosorbent assay (ELISA) double antibody sandwich assay. Colloidal gold immunochromatography assay was used to detect serum N protein antibodies in the above populations. Fifty cases of SARS-CoV-2 nucleic acid-positive and SARS-CoV-2 antibody-negative patients had a serum N protein positivity rate of 76%. Thirty-seven patients who were positive for serum SARS-CoV-2 antibody after infection had a serum SARS-CoV-2 N protein positivity rate of 2.7%. Serum N protein test results of 633 non-SARS-COV-2 infected patients, including pregnant women, patients with other respiratory infections, and individuals with increased rheumatoid factor were all negative, with serum N protein concentration <10.00 pg/mL at 100% specificity. Using SPSS 19.0 to calculate the receiver operating characteristic curve, the area under the curve was determined to be 0.9756 (95% confidence interval 0.9485-1.000, < 0.0001), and sensitivity and specificity were 92% (95% confidence interval 81.16-96.85%) and 96.84% (95% confidence interval 95.17-97.15%), respectively. The best CUT-OFF value was 1.850 pg/mL. The measurement of serum SARS-COV-2 N protein has a high diagnostic value for infected patients before the antibody appears and shortens the window period of serological diagnosis. It is recommended that the manufacturer establish two different CUT-OFF values according to the purpose of the application. One CUT-OFF value is used for the diagnosis of clinical SARS-COV-2 infection, and the other is used to screen out as many suspected cases as possible.